Business finance - Peirson, Graham (McGraw-Hill (Australia), 1995)
Peirson's has been the market leading Business Finance text in Australia for nearly 30 years. Over that time, "Business Finance" has been updated and reinvented in response to the changing requirements of finance students building a reputation for providing a current, authoritative and comprehensive introduction. It's broad coverage makes it suitable for one or two subject programs, at both undergraduate and postgraduate levels. This eighth edition has been thoroughly updated and refined to ensure its continued relevance to the Australian market. The authors have pitched the text to suit the needs of today's students, making it even more readable but without compromise to the content.